How old are you—Evaluation of age reading methods for the invasive round goby (Neogobius melanostomus, Pallas 1814). (19th December 2017) - Florin, A.‐B.; Hüssy, K.; Blass, M.; Oesterwind, D.; Puntila, R.; Ustups, D.; Albrecht, C.; Heimbrand, Y.; Knospina, E.; Koszarowski, K.; Odelström, A.
Summary: In the Baltic, the first observation of the round goby ( Neogobius melanostomus, Pallas 1814) was made in 1990. Within the past decade the species became invasive and spread rapidly throughout the Baltic Sea. Studies about the fishes potential impacts on resident species promote the need for an increasing knowledge of their basic stock structures such as growth rates, longevity and mortality, which all rely on accurate estimates of age. Former studies on the round goby have used several different age reading techniques. In this study, we compared three standard otolith preparation methods for ageing and present the best procedure for the invasive round goby. The results showed significant differences in age estimates of the same fish between the different preparation methods and between readers. The estimation of the first annulus, the first year, was the most problematic. The overall agreement was lowest when reading the whole otoliths while the best performance was achieved with sectioned and stained preparation method. Depending on method used the growth estimates also differed. The results question comparability between previous studies and highlight the importance of harmonised aging procedures for the round goby for obtaining correct estimates of population parameters such as growth rate, age at maturity, and longevity.